Controlled-release nanofertilizer using chitosan nanoparticles loaded with NPK: Development and impact on the yield and nutritional quality of Solanum tuberosum - Marquez Cazorla, Jessica Ingrid (2025)
In recent years, nanotechnology has made significant progress in various fields, including agriculture, where nanofertilizers play a pioneering role in improving crop productivity and reducing environmental pollution. In this study, a controlled-release nanofertilizer was developed using chitosan nanoparticles loaded with nitrogen (N), phosphorus (P), and potassium (K). The chitosan nanoparticles (CS-NPs) were prepared via an ionic gelation method using sodium tripolyphosphate and characterized by scanning transmission electron microscopy and infrared spectroscopy. The results revealed that the nanoparticle size ranged from 17.21 nm to 18.32 nm. The controlled release of N, P, and K was evaluated over 240 hours. The nanofertilizer was then applied foliage to Solanum tuberosum seedlings under greenhouse conditions. The findings indicated that the 0.25% chitosan nanofertilizer formulation resulted in nanoparticles with relatively high nutrient absorption capacity, with average values of 4.65 mg/L nitrogen, 198.55 mg/L phosphorus, and 1345.27 mg/L potassium. However, the most effective nanofertilizer treatment was the 1% chitosan nanoparticle formulation loaded with 5 ppm N, P, or K, resulting in the best nutritional characteristics among all the fertilization treatments and a 37% increase in the mass yield of Solanum tuberosum compared with that of the control. These results suggest that NPK-loaded chitosan nanoparticles could be used as foliar sprays to produce more nutritious and higher-yielding crops.